Social Participation of Students With Special Educational Needs in Mainstream Education 2020
DOI: 10.4324/9780429264184-4
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and friendship quality of students with special educational needs in regular Greek primary schools

Abstract: The study addresses the social participation of integrated students with special educational needs (SEN) in upper primary regular classes in Greece alongside their perceptions of best friend quality. In keeping with previous research, social participation was defined as consisting of four key dimensions, namely the students' acceptance by classmates; their friendships; their social self-perceptions; and their social interactions. Participants were 457 students with a mean age of 11.04 (sd=.83), of which 45 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…They may face greater prejudice (Avramidis, 2010) and bullying (Rose, Monda-Amaya, & Espelage, 2010), and are at a greater risk to feel excluded at schools (Grütter et al, 2017;Schwab et al, 2013;Schwab, INCLUSION AND DIFFICULTIES IN INCLUSIVE SCHOOLS 6 2017). Recent large-scale studies found that students with SEN felt less included at school (Stiefel, Shiferaw, Schwartz, & Gottfried, 2017) and that they had fewer friends and experienced negative peer relationships than other students (Avramidis, Avgeri, & Strogilos, 2018;Banks et al, 2017;Huber, Gerullis, Gebhardt, & Schwab, 2018). A lack of inclusion is also related to many negative emotional-developmental outcomes, including depression, (McGraw, Moore, Fuller, & Bates, 2008), substance abuse, and other mental health problems (Arslan, 2018;Bond et al, 2007), as well as poorer academic outcomes (Szumski & Karwowski, 2015;van Ryzin, Gravely, & Roseth, 2009) such as a reduced academic selfconcept (Bear, Minke, & Manning, 2002).…”
Section: Socioemotional Inclusion and Academic Self-conceptmentioning
confidence: 99%
“…They may face greater prejudice (Avramidis, 2010) and bullying (Rose, Monda-Amaya, & Espelage, 2010), and are at a greater risk to feel excluded at schools (Grütter et al, 2017;Schwab et al, 2013;Schwab, INCLUSION AND DIFFICULTIES IN INCLUSIVE SCHOOLS 6 2017). Recent large-scale studies found that students with SEN felt less included at school (Stiefel, Shiferaw, Schwartz, & Gottfried, 2017) and that they had fewer friends and experienced negative peer relationships than other students (Avramidis, Avgeri, & Strogilos, 2018;Banks et al, 2017;Huber, Gerullis, Gebhardt, & Schwab, 2018). A lack of inclusion is also related to many negative emotional-developmental outcomes, including depression, (McGraw, Moore, Fuller, & Bates, 2008), substance abuse, and other mental health problems (Arslan, 2018;Bond et al, 2007), as well as poorer academic outcomes (Szumski & Karwowski, 2015;van Ryzin, Gravely, & Roseth, 2009) such as a reduced academic selfconcept (Bear, Minke, & Manning, 2002).…”
Section: Socioemotional Inclusion and Academic Self-conceptmentioning
confidence: 99%
“…However, especially for the investigation of the social dimension of inclusion, a broader view with which to examine this topic is required. Aside from SEN (e.g., Avramidis, Avgeri, and Strogilos, 2018; Schwab, 2015b, 2016), gender differences (e.g., Ato, Galián, and Fernández‐Vilar, 2014) or a migrant biography (Graham, Taylor, and Ho, 2009; Hamel, Schwab, and Wahl, 2021, 2022; Krull, Wilbert, and Hennemann, 2018) have been proposed as crucial factors that have a negative impact on students’ social participation.…”
Section: Introductionmentioning
confidence: 99%
“…Across all these dimensions, the lack of social participation amongst students with SEN has been repeatedly reported. Students with SEN have been found to have fewer friends than their classmates without SEN (Avramidis, Avgeri, and Strogilos, 2018; Bossaert et al., 2015; Frostad, Mjaavatn, and Pijl, 2011; Schwab, 2015a, b). Similar negative outcomes for students with SEN have been found in relation to the perceived quality of friendships (Hoffmann et al., 2020; Locke et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, peer relationships also depend on the school peer context. Research on inclusive classrooms suggests that individuals with ID are often less well accepted, interact less with others and have fewer friends compared to their typically developing classmates (Avramidis, Avgeri and Strogilos, ; Tipton et al, ). However, not all students with ID attend inclusive classrooms; a substantial number attend special needs classrooms where all peers in the classrooms exhibit difficulties in intellect and adaptive behaviours.…”
Section: Introductionmentioning
confidence: 99%